Photoprotection in the green tidal alga Ulva prolifera: role of LHCSR and PsbS proteins in response to high light stress. (19th July 2013) - Mou, S.; Zhang, X.; Dong, M.; Fan, X.; Xu, J.; Cao, S.; Xu, D.; Wang, W.; Ye, N.
Abstract: Ulva prolifera, an intertidal macroalga, has to adapt to wide variations in light intensity, making this species particularly rewarding for studying the evolution of photoprotective mechanisms. Intense light induced increased non‐photochemical quenching (NPQ) and stimulated de‐epoxidation of xanthophyll cycle components, while DTT‐treated samples had lower NPQ capacity, indicating that the xanthophyll cycle must participate in photoprotection. In this work, we found that the PsbS‐related NPQ was maintained in U. prolifera . According to analysed gene expression, both Lhc SR and psb S were up‐regulated in high light, suggesting that these two genes are light‐induced. LHCSR and PsbS proteins were present at different light intensities and accumulated under high light conditions, and PsbS concentrations were higher than LHCSR, showing that the NPQ mechanism of U. prolifera is more dependent on PsbS protein concentration. Moreover, the level of both LHCSR and PsbS proteins was high even in the darkness, and neither the transcript level nor protein content of Lhc SR and psb S genes varied significantly following short‐term exposure to intense light. These findings suggest that this alga can modulate NPQ levels through regulation of the xanthophyll cycle and concentrations of PsbS and/or LHCSR.